Knowledge mapping of research on Industry 4.0: a visual analysis using CiteSpace - Stojanović, Anđelka (Serbian Journal of Management, 2022)
This study aims to explore thematic networks in research of Industry 4.0 in recent years. The analysis presented in the paper is based on the data retrieved from the Web of Science about publications that included the terms "fourth industrial revolution" and "Industry 4.0" within the domain of business application. The research consisted of a general analysis of publications and a more detailed analysis conducted using CiteSpace. CiteSpace, one of the very popular visual analysis tools for mapping the scientific networks, was used to analyze extracted articles and identify existing networks, clusters, and most influential authors. The findings indicate that Industry 4.0 represents a well-developed research field with distinctive but complementary research topics and also points out the emerging research topics. The study results can be helpful in further research on Industry 4.0 and relating technologies because it indicates the direction of recent research development.